2012
DOI: 10.1111/j.1523-1739.2012.01955.x
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Effects of Water Quality on Threatened California Salamanders but Not on Co‐Occurring Hybrid Salamanders

Abstract: Biological invasions and habitat alteration are often detrimental to native species, but their interactions are difficult to predict. Interbreeding between native and introduced species generates novel genotypes and phenotypes, and human land use alters habitat structure and chemistry. Both invasions and habitat alteration create new biological challenges and opportunities. In the intensively farmed Salinas Valley, California (U.S.A.), threatened California tiger salamanders (Ambystoma californiense) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Their results demonstrate how the displacement of native genotypes can potentially compromise ecosystems by generating novel genotypes and phenotypes. Ryan et al (2013) also found that salamanders with hybrid genotypes were able to survive major environmental stress while native genotypes could not. All native genotype salamanders died off unless they had already metamorphosed prior to die-off events.…”
Section: Reviewsmentioning
confidence: 93%
“…Their results demonstrate how the displacement of native genotypes can potentially compromise ecosystems by generating novel genotypes and phenotypes. Ryan et al (2013) also found that salamanders with hybrid genotypes were able to survive major environmental stress while native genotypes could not. All native genotype salamanders died off unless they had already metamorphosed prior to die-off events.…”
Section: Reviewsmentioning
confidence: 93%
“…It breeds primarily in vernal pools and faces threats from extensive habitat conversion to agricultural lands (Davidson et al 2002), pesticide usage (Ryan et al 2012) and hybridization with the invasive barred tiger salamander [Ambystoma (tigrinum) mavortium, BTS], which was introduced to California in the 1950s (Riley et al 2003). Our laboratory has been working on this system for the past 20 years, and we have, along with others, learned a great deal about tiger salamanders in California by studying their molecular ecology.…”
Section: Methods and Their Applications To Amphibiansmentioning
confidence: 99%
“…Hybridization with the invasive BTS is among the greatest threats facing CTS. Hybrid animals are more robust and have increased survival rates compared to pure native CTS, leading to concerns that hybrids will be strongly favoured by natural selection and replace pure CTS (Fitzpatrick & Shaffer 2007b;Ryan et al 2012). Additionally, the presence of CTS/BTS hybrids has been found to negatively impact other amphibians breeding in the same ponds Searcy et al 2015).…”
Section: Methods and Their Applications To Amphibiansmentioning
confidence: 99%
“…In a series of papers, our laboratory has demonstrated that nonnative A. t. mavortium introduced into central California in the 1950s led to the formation of a hybrid swarm in approximately 25% of the range of the federally and state-protected California tiger salamander (A. californiense); another 25% has been invaded by a smaller set (3/68 marker loci) of superinvasive genes that are spreading more rapidly (46,59,60). At both the phenotypic and genetic levels, these hybrids generally have higher fitness than pure native salamanders, raising serious conservation concerns for the endangered A. californiense (61)(62)(63)(64).…”
Section: Hybridizationmentioning
confidence: 98%